Identifying and Understanding Cultural Differences in the Online Classroom - Karen L. Milheim; Christy B. Fraenza (Adult Education Research Conference, 2014)
The purpose of this study is to examine how online course instructors identify cultural differences among students in the classroom. In addition, the study explores how knowing students' cultural backgrounds and cultural norms can prepare instructors to facilitate among varied learning styles, values, and perceptions within a course. The findings lead to a better understanding of how instructors in online course settings can better identify and attend to the learning styles and needs of students in light of cultural differences.